Probabilistic Fretting Fatigue Analysis of Bridge Stay Cables at Saddle Supports. Issue 4 (1st October 2020) - Chehrazi, Ali; Walbridge, Scott; Mohareb, Sherif; Goldack, Arndt; Schlaich, Mike
Abstract: Saddle systems have been used on recent projects to support the cables in cable-stayed and extradosed bridge structures. A major design consideration for these anchorage systems is the in-service fretting fatigue behaviour of the cables within the pylon saddle. In order to better understand the fatigue behaviour of these anchorage systems, a research project was undertaken, wherein fatigue tests were performed on saddle test specimens, analytical models for calculating displacements and contact forces were developed, and a multiaxial stress-based fretting fatigue model was developed for calculating fatigue life. In the current paper, it is shown how the developed models can be used to perform probabilistic analysis of fretting fatigue life for the purpose of assessing the fatigue reliability of saddle systems, using two approaches – fretting maps, in conjunction with Monte Carlo simulation (MCS) or the multiplicative dimensional reduction method (MDRM).